Całka stochastyczna Ito - definicja i jej własności - Posacka, Katarzyna (Ito stochastic integrals - definition and some properties, 2005)
The main purpose of this paper is to present definition Ito integrals and their properties. There is shown formula Ito, which can be used for stochastic differential equations like: dX,= fiX'dt + odW,, where X - unknown stochastic process, /i, cr - known functions, W - Wiener process.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (15); 2005; nr 1096, s. 309-317